2020
DOI: 10.1002/bjs.11561
|View full text |Cite
|
Sign up to set email alerts
|

Stent as a bridge to surgery or immediate colectomy for malignant right colonic obstruction: propensity-scored, national database study

Abstract: Background The aim of this study was to compare perioperative outcomes of urgent colectomy and placement of a self‐expanding metallic stent followed by colectomy for patients with malignant right colonic obstruction. Right‐sided malignant obstruction is less common than left‐sided. Stenting for malignant left colonic obstruction has been reported to reduce postoperative complications. However, the impact of stenting for malignant right colonic obstruction remains undefined. Methods The study included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…Multivariate Cox proportional hazards model was used to analyze the risk factors related with the prognosis. Then, these covariates were matched by PSM with the allowable error at 0.3 (7)(8)(9) to compare the differences between the patients with RHCC and NHCC. The ratio of RHCC and NHCC patients was 1:4 in the PSM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate Cox proportional hazards model was used to analyze the risk factors related with the prognosis. Then, these covariates were matched by PSM with the allowable error at 0.3 (7)(8)(9) to compare the differences between the patients with RHCC and NHCC. The ratio of RHCC and NHCC patients was 1:4 in the PSM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analysis showed that smoking is an independent risk factor for CA, and the smoking rate of CA patients was ~4% higher than that of UA patients in the present study, as in previous reports. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 A study of twins found that smoking is a risk factor for appendicitis, especially in women. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 10 It contains discharge abstracts and administrative reimbursement claim data from inpatient cases collected at participating hospitals, and it has been used in various studies. 11 , 12 Details of this database have been reported by Yamana et al 13 The database includes the following data: disease names, hospitalization costs, urgent or planned hospital admission, comorbidities at admission and during hospitalization, coded according to the International Statistical Classification of Diseases and Related Health Problems, 10th revision (ICD‐10), age, sex, length of hospital stay (LOS), medical procedures including surgery, names and quantities of medicines administered, and discharge status (including in‐hospital deaths). Medical procedures are indexed with a Japanese code (K‐code, Table S1 ), 14 assigned by the Ministry of Health, Labor, and Welfare of Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Using the claims data for procedures performed during postoperation hospitalization, we also created 17 candidate procedure variables that could indicate postoperative infections. Variable selection was based on previous studies using the DPC database 18–21 and clinical relevance (e.g., addition of intravenous antibiotics and drainage duration). Candidate procedure variables are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The features of the DPC data include subcategorized secondary diagnoses and detailed daily procedure records 17 . Numerous studies on therapeutics for patients who underwent surgery have been conducted using the DPC Study Group database 18–21 . A previous study assessed the validity of diagnosis and procedure records in the DPC data 22 ; however, the study targeted the diagnoses present on admission.…”
Section: Introductionmentioning
confidence: 99%